Using the Associative Property, we can rearrange the terms within the parentheses:
2(a + 5) + 4(2a + 3) - 10
= 2a + 10 + 8a + 12 - 10
= 2a + 8a + 10 + 12 - 10
Now, combining like terms gives:
2a + 8a + 10 + 12 - 10
= 10a + 22 - 10
Finally, applying the Commutative Property allows us to rearrange the terms:
10a + 22 - 10
= 10a - 10 + 22
= 10(a - 1) + 22
Therefore, the expression equivalent to 2(a + 5) + 4(2a + 3) - 10 using the Associative and Commutative Properties is 10(a - 1) + 22.
Apply the Associative and Commutative Properties to generate an expression equivalent to 2(a+5)+4(2a+3)−10 .(
1 answer